Shark Attacks and Shark Diving Reply - Barreiros, Joao Pedro; Gadig, Otto B. F. [UNESP]; Haddad, Vidal [UNESP] (Elsevier B.V., 2015)
It is with great astonishment and concern that I read the letter to the editor by Barreiros et al1 in which the authors report an attack by a blue shark on a spear fisherman in the Azores. Whereas the first part of the article accurately details the circumstances of the accident, Barreiros et al, in the second part, devise a far-fetched and illegitimate connection with shark diving, in particular with shark feeding.